Food and Beverage Service Standards at Capella Ubud during the Covid-19 Pandemic - I Made Bayu Kusuma; I Gusti Agung Mas Krisna Komala Sari; Ni Ketut Bagiastuti; I Ketut Suja (International Journal of Glocal Tourism, 2023)
Purpose: The purpose of this study is to determine the application of service standards for food and beverage service by employees at the Capella Ubud, Bali, Indonesia, during the Covid-19 pandemic. Research methods: This study uses descriptive analysis methods and descriptive statistics using guest comments. The data obtained by finding the average value of the results of guest comments with 3 indicators namely location, service, and cleanliness so that data presentation can be carried out to draw conclusions. Findings: The results of this study indicate that the location, service, and cleanliness indicators get guest satisfaction with an average 4-star gain of 151.16 with the highest score on cleanliness and an average 5-star score of 148.84 with the highest score on service. Implication: Capella Ubud applies good food and beverage service standards during the Covid-19 pandemic.